José Oroz Reta, Virgilio: vida, obras, fortuna. Salamanca, Universidad Pontificia, 1990, 231 pp. (Bibliotheca Salmanticensis, Estudios 35) - Cavallero, Pablo A. (1995)
Fil: Cavallero, Pablo A. Pontificia Universidad Católica Argentina; Argentina